Analisis Corporate Social Responsibility Dalam Aspek Perpajakan Dan Pengaruhnya Terhadap Penghindaran Pajak - Gerardo B. S. Dewangga, Agus Bandiyono, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2020)
The obligations to implement CSR in Indonesia is regulated in the Limited Liability Company Law. The disclosure of CSR implementation can be stated by the company in a sustainability report. The tax regulations in Indonesia do not directly regulate the term CSR. In addition, the implementation of CSR can be used as a means of tax avoidance by companies because there are costs for implementing CSR that are deductible. Therefore, this study was conducted to analyze the concept of CSR in the Indonesian taxation aspect, conduct a descriptive analysis of CSR disclosure in the sustainability report, and determine the effect of CSR disclosure on tax avoidance actions in the major financial company listed on IDX. The first result of this research is that the CSR obligation holders according to the Company Law are also the Subjects of Corporate Tax in the Income Tax Law. Costs related to the implementation of CSR have not been regulated directly in the Income Tax Law. However, there are some costs that are consistent with the CSR disclosure standards in GRI G4. Second, the average CSR disclosure by major financial service companies on the IDX is only 27.2%. Third, this study shows that CSR disclosure has no effect on tax avoidance.